The Value of Thrombus Markers Applied in Patients with Respiratory Failure: Thrombus Markers in Respiratory Failure - Chen, Yingqun; Yin, Zihan; Wang, Junshi; Yan, Cunliang; Lin, Xuwei; Huang, Lei (Journal of Medical Biochemistry, 2024)
Background: This work assessed the value of novel thrombus markers—thrombin-antithrombin complex (TAT), plasmin-α2-plasmin inhibitor complex (PIC), thrombomodulin (TM), and tissue plasminogen activator-inhibitor complex (t-PAIC) applied in patients with respiratory failure (RF), including their role in predicting thrombus formation, evaluating prognosis, and assessing disease severity. Methods: eighty patients with RF were enrolled and categorized into mild (n = 10), moderate (n = 9), and severe (n = 71) groups based on disease severity. Meanwhile, patients were also classified into thrombus (n = 14) and non-thrombus (n = 76) groups based on the presence of thrombus. Furthermore, they were assigned into survival (n = 70) and death (n = 20) groups based on prognosis. Traditional coagulation indicators, thrombus markers, infection-related parameters, and respiratory-related indicators were compared among patients in different groups. This work explored the predictive effects of these indicators on the degree of respiratory failure, thrombus formation, and prognosis in various patient groups. Additionally, correlations of thrombus markers and traditional coagulation indicators to respiratory-related indicators and infection-related indicators were analyzed. Results: upon admission, levels of thrombin-antithrombin complex (TAT), plasmin-α2-plasmin inhibitor complex (PIC), and tissue plasminogen activator-inhibitor complex (t-PAIC) in the thrombus group were sharply higher in contrast to those in the non-thrombus group, showing obvious differences (P<0.05). Patients in the death group experienced remarkably elevated TAT, PIC, t-PAIC, thrombomodulin (TM), and to the survival group (P<0.05). In addition, high-sensitivity C-reactive protein (hs-CRP) in the death group was higher to that in the survival group (P<0.05). Platelet count (PLT) and procalcitonin (PCT) were sharply lower in the survival group (P<0.05). In groups of varying severity, PCT exhibited an elevated level in the severe, demonstrating great differences to the mild to moderate groups (P<0.05). Besides, TAT, PIC, TM, and t-PAIC showed higher sensitivity and accuracy in predicting severe RF, with higher specificity in predicting thrombus formation in RF patients. In correlation analysis, a positive correlation was observed between TT, PCT, and the fraction of inspired oxygen (FiO2). The activated partial thromboplastin time (APTT), PCT, and FiO2 exhibited positive correlations. Additionally, a positive association existed between fibrinogen (FIB), hs-CRP, and PLT. A positive link was identified between D-dimer and hs-CRP, PIC and PLT, as well as t-PAIC and PCT. Conclusion: Thrombus markers exerted a crucial effect in patients experiencing respiratory failure, serving as pivotal indicators for assessing the severity of the condition, identifying thrombotic risk, and predicting prognosis.